STUDENT PARENT PERCEPTION TOWARDS CONSUMER BASED BRAND EQUITY - Jilly Jo Haryanto; Andy Susilo Lukito Budi (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2011)
It can be argued that parental role in selecting which university should a student candidate take is instrumental. With the rapidly growing Indonesia higher education industries over the last ten years, study in brand equity area focussing on the parent’s perception towards the brand equity of a university become more and more crucial. This study investigates student parent’s perception using five variables of consumer based brand equity from Lassar et al. (1995) in a private university in Jakarta (University X). There are two different departments to be compared with in order to know whether there are differences in brand equity perception between student parents from both departments. The result shows most variables are indifference with exceptions in three questions and the three questions relate to performance and attachment concerning quality and long-term commitment. Implication and suggestion have been promoted according to the result.